Kualitas Sperma Beku Sapi Bali dalam Pengencer Air Kelapa Modifikasi dengan Berbagai Aras Dimethyl Sulfoxide (FROZEN SPERM QUALITY OF BALI BULLS IN MODIFIED COCONUT WATER EXTENDER WITH DIFFERENT DIMETHYL SULFOXIDE CONCENTRATION) - Hine, Thomas Mata; Uly, Kirenius; Nalley, Wilmientje Marlene; Armadianto, Heri (Jurnal Veteriner, 2019)
Dimethyl Sulfoxide (DMSO) is one type of cryoprotectant which has a low molecular weight so that it is easier to enter cells when cryopreservation. The purpose of this study was to explore the optimal concentration of DMSO in modified coconut water (mCW) extender that were able to maintain frozen sperm quality of bali bulls. Semen was collected from two four-year old bali bulls by artificial vagina. Good quality semen diluted with mCW (young coconut water + 20% egg yolk + 7.5 % moringa leaf extract) and supplemented by 3, 5, or 7% DMSO. Semen was filled into 0.25 ml ministraw, and was incubated in a refrigerator at 5°C for four hours, frozen on the surface of liquid nitrogen for 10 minutes and then dipped into liquid nitrogen. The quality of post thawing sperm was measured 24 hours later by placing the ministraw of frozen semen into water at 37oC for 30 seconds. Data were analyzed by analysis of variance and continued with Duncan test. Postthawing observations showed that bali bulls sperm cryopreserved at 3% DMSO yielded higher motility and viability (p<0.05) i.e. 36 and 44.15%, than DMSO 5% i.e. 18 and 23.65%, and DMSO 7% i.e. 7 and 12.62%. The recovery rate of sperm cryopreserved at 3% DMSO was also higher (p<0.05) than DMSO 5 and 7%, successively 45.65, 23.06, and 8.86%. The results of this study concluded that the optimal concentration of DMSO in mCW diluent to maintain frozen sperm quality of bali bulls was 3%.